Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Join our Q&A platform and get accurate answers to all your questions from professionals across multiple disciplines. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

Find the values of [tex]\(a\)[/tex] and [tex]\(b\)[/tex] for the following expression:

[tex]\[
\frac{1-\sqrt{3}}{1+\sqrt{3}} = a + b\sqrt{3}
\][/tex]


Sagot :

Sure! Let's solve the given problem step-by-step and find the values of [tex]\(a\)[/tex] and [tex]\(b\)[/tex] for the expression [tex]\(\frac{1 - \sqrt{3}}{1 + \sqrt{3}}\)[/tex].

1. Given Expression:
[tex]\[ \frac{1 - \sqrt{3}}{1 + \sqrt{3}} = a + b \sqrt{3} \][/tex]

2. Rationalizing the Denominator:
To rationalize the denominator, we'll multiply both the numerator and the denominator by the conjugate of the denominator. The conjugate of [tex]\(1 + \sqrt{3}\)[/tex] is [tex]\(1 - \sqrt{3}\)[/tex].

[tex]\[ \frac{1 - \sqrt{3}}{1 + \sqrt{3}} \times \frac{1 - \sqrt{3}}{1 - \sqrt{3}} = \frac{(1 - \sqrt{3})^2}{(1 + \sqrt{3})(1 - \sqrt{3})} \][/tex]

3. Simplify the Expression:
- Denominator:
[tex]\[ (1 + \sqrt{3})(1 - \sqrt{3}) = 1^2 - (\sqrt{3})^2 = 1 - 3 = -2 \][/tex]

- Numerator:
[tex]\[ (1 - \sqrt{3})^2 = 1^2 - 2 \cdot 1 \cdot \sqrt{3} + (\sqrt{3})^2 = 1 - 2\sqrt{3} + 3 = 4 - 2\sqrt{3} \][/tex]

Therefore, our rationalized fraction is:
[tex]\[ \frac{4 - 2\sqrt{3}}{-2} \][/tex]

4. Separate the Fraction:
[tex]\[ \frac{4 - 2\sqrt{3}}{-2} = \frac{4}{-2} - \frac{2\sqrt{3}}{-2} = -2 + \sqrt{3} \][/tex]

5. Identifying [tex]\(a\)[/tex] and [tex]\(b\)[/tex]:
Comparing [tex]\(-2 + \sqrt{3}\)[/tex] with [tex]\(a + b\sqrt{3}\)[/tex], we get:
[tex]\[ a = -2 \][/tex]
[tex]\[ b = 1 \][/tex]

Therefore, the values of [tex]\(a\)[/tex] and [tex]\(b\)[/tex] are:
[tex]\[ a = -0.2679491924311228 \][/tex]
[tex]\[ b = 1.7320508075688772 \][/tex]